2004
DOI: 10.1002/hup.610
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of a carbamazepine–mianserin combination scheme in opiate detoxification

Abstract: A recent comparative randomized double-blind study has suggested the utility of a carbamazepine/mianserin combination as a treatment for opiate withdrawal. The aim of the present study was to explore the feasibility and efficiency of this combination under naturalistic conditions. Five hundred and fifty mostly polysubstance abusing patients treated with a standardized scheme combining carbamazepine and mianserin were assessed with regard to deviations to the protocol, used co-medications and retention in treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…On the other hand, the fact that 7/10 patients on the carbamazepine/mianserin combination, and 9/10 patients on clonidine required dosage reductions may lead to the question of excessive initial doses. However, the carbamazepine/ mianserin dosing scheme was identical to the procedure used in the study reported by Bertschy et al (21), which we subsequently have found to be applicable in every day practice (22). The dosage regime used in our inpatient unit can be considered to be in the medium dose range compared to previously published studies (40), which generally began with 0.1-0.2 mg/dose (0.15 in our patients), increasing to a maximum of around 1 mg/day (0.6 in our clonidine-scheme).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the fact that 7/10 patients on the carbamazepine/mianserin combination, and 9/10 patients on clonidine required dosage reductions may lead to the question of excessive initial doses. However, the carbamazepine/ mianserin dosing scheme was identical to the procedure used in the study reported by Bertschy et al (21), which we subsequently have found to be applicable in every day practice (22). The dosage regime used in our inpatient unit can be considered to be in the medium dose range compared to previously published studies (40), which generally began with 0.1-0.2 mg/dose (0.15 in our patients), increasing to a maximum of around 1 mg/day (0.6 in our clonidine-scheme).…”
Section: Discussionmentioning
confidence: 90%
“…The two treatments did not differ in the intensity of the withdrawal, according to the rate of retention in treatment, symptoms and psychic distress. We have recently assessed the efficiency of the carbamazepine/mianserin combination under naturalistic conditions in 550 patients, and found a completion rate of 63% (22).…”
Section: Introductionmentioning
confidence: 99%
“…Carbamazepine is an antiepileptic agent that is generally used as a third-line treatment for neuropathic pain 28 . Carbamazepine stabilizes presynaptic neuronal membranes by inhibiting sodium channels, resulting in a reduction of neurotransmitter release and action potential conductance in nociceptive fibers 29 . Carbamazepine can also potentiate GABA receptors 30,31 , interrupt the glutamatergic function via N-methylD-aspartate receptors, and block calcium channel-modulated central sensitization, which is related to its anti-nociceptive, but not its anticonvulsant effects 32, 33 .…”
Section: Elriah-pc Medical Journal Ofmentioning
confidence: 99%